The Violence Risk Scale: Predictive Validity and Linking Changes in Risk With Violent Recidivism in a Sample of High- Risk Offenders With Psychopathic Traits. (April 2013) - Lewis, Kathy; Olver, Mark E.; Wong, Stephen C. P.
The Violence Risk Scale (VRS) uses ratings of static and dynamic risk predictors to assess violence risk, identify targets for treatment, and assess changes in risk following treatment. The VRS was rated pre- and posttreatment on a sample of 150 males, mostly high-risk violent offenders many with psychopathic personality traits. These individuals attended a high-intensity institution-based cognitive–behavioral–oriented violence reduction treatment program in Canada and were then followed up for approximately 5 years postrelease to determine court adjudicated community violent recidivism. VRS scores significantly predicted violent recidivism. Measurements of risk reduction using dynamic VRS predictors were significantly correlated with reduction of violent recidivism after controlling for various potential confounds. The results suggest that, in a high-risk group of offenders with significant psychopathic traits, the VRS demonstrated predictive validity and the dynamic predictors can be used to assess treatment progress, which is linked to a specific criterion variable, thus, fulfilling the criteria for causal dynamic predictors set forth by Kraemer et al.